A slice based approach to recognize and extract free-form volumetric features in a CAD mesh model. Issue 5 (2nd September 2016) - Adhikary, Nepal; Gurumoorthy, B.
ABSTRACT: This paper describes an algorithm to recognize and extract volumetric features by directly clustering the triangles constituting a feature in a CAD mesh model. The algorithm involves two steps – isolating features in 2D slices followed by a 3D traversal to cluster all the triangles in the feature. The main advantage of this approach is that processing of the three dimensional mesh occurs only for the triangles associated with its signature identified on the 2D slice. Results from an implementation tested on various mesh models are presented. GRAPHICAL ABSTRACT: